Distribution of transport mobility of city population between individual and public transport - Доля, Віктор Костянтинович; Іванов, Ігор Євгенович (Technology audit and production reserves, 2013)
A number of recent studies shows that the organization and planning of urban public transport lies in accurate calculation or forecasting of the distribution between the individual and public transport. Previously, it was believed that the potential movement is carried out by transport and on foot. But today it is necessary to define the coefficients of using transport and urban public transport, depending on a set of factors and different percentage of the major population groups. This article has grouped the major impacts on the transportation mobility, according to foreign and domestic researches and obtained during the survey of urban residents. That would allow to take into account the effects of changes in the social, economic and technical indicators when determining the parameters of the transport system of the cities,. As a result of these investigations, the data array was obtained which contains the transport using coefficients and public transport using coefficients for the researched cities. The revealed set of factors influencing the transport mobility allows overall estimation of the distribution of urban residents traveling either by the individual or public transport.